Impacts of Ethnocentrism and Country of Origin on Purchase Decision in Tanzania - Mbwiga, Grace Edward (2024)
The decades’ old evolution of country-of-origin studies have led to the rise and development of consumer ethnocentrism concept as one of the factors leading to country-of-origin bias. From the development of a CETSCALE (Shimp & Sharma, 1987), an instrument that has paved the way for more research in the area, to the application of it to various countries across the world, to the modification and application of it to various countries across the globe. Consumer ethnocentrism is still a broad and new topic to be explored in most of the developing countries, particularly in the African continent where a gap in the area can be observed. The current study aims to identify the presence of ethnocentric behaviours among Tanzanian consumers of juice and spirit products located in Dar es Salaam and how different socioeconomic factors influence consumer ethnocentrism behaviours. In addition, it also aims to determine the extent to which country of origin bias affects buying decisions of Tanzanian consumers in the two product categories mentioned. A modified version of the CETSCALE and country of origin questionnaires with different demographic factors were conducted among the 100 and 15 respondents in juice and spirit categories, respectively. The data obtained was analysed through SPSS 25 where the mean score of the questionnaire and respective items was determined to find out the level of ethnocentrism and country of origin effect among the participants, Analysis of Variance (ANOVA) test was conducted to determine the relationship between the different socioeconomic factors such as age, education and level of income and the level of ethnocentrism, in addition, parametric tests for normally distributed data in the form of independent sample tests were used for demographic factors such as gender to determine its relation to consumer ethnocentric behaviours.